Bacterial invasion into the epidermis of rats with sodium lauryl sulphate‐irritated skin increases damage and induces incontinence‐associated dermatitis. Issue 1 (2nd August 2022) - Koudounas, Sofoklis; Minematsu, Takeo; Mugita, Yuko; Nakai, Ayano; Tobe, Hiromi; Takizawa, Chihiro; Kunimitsu, Mao; Nakagami, Gojiro; Sanada, Hiromi
Abstract: Incontinence‐associated dermatitis (IAD) is caused by prolonged exposure to urine/liquid stool. It is a common and often painful skin condition in older incontinent adults because of poor prevention. Patients with urinary infections are at risk of developing IAD, and to guide the development of novel prevention strategies, we aimed to develop an animal model of IAD by urine and bacteria. First, contralateral sites on the dorsal skin of Sprague–Dawley rats were compromised by sodium lauryl sulphate (SLS), simulating frequent cleansing with soap/water. Filter discs were then placed inside ring‐shaped chambers on foam dressings, inoculated with or without Pseudomonas aeruginosa, covered with agarose gels immersed in cultured filtrated urine, and secured in place with an occlusive dressing for 3 days. Untreated and SLS‐compromised sites served as controls. The IAD was developed at bacteria‐inoculated sites, characterised by severe IAD‐like redness that persisted for up to 3 days post‐exposure and higher disruption of the skin barrier function compared with non‐inoculated sites. Pathological changes included epidermal thickening, partial skin loss, inflammatory cell infiltration, accumulation of red blood cells, and invasion of bacteria into the epidermis. This novel, clinically relevant IAD rat model can serve for future prevention developments.